Exploring Biofilm-Related Traits and Bile Salt Efficacy as Anti-Biofilm Agents in MDR Acinetobacter baumannii - Verica Aleksic Sabo; Dušan Škorić; Suzana Jovanović-Šanta; Petar Knezevic (MDPI AG, 2024)
Acinetobacter baumannii has been designated as a critical priority pathogen by the World Health Organization for the development of novel antimicrobial agents. This study aimed to investigate both the phenotypic and genotypic traits of multidrug-resistant (MDR) A. baumannii strains, along with the effects of natural bile salts on biofilm formation. The research analyzed phenotypic traits, including autoaggregation, hydrophobicity, twitching motility, lectin production, and biofilm formation, as well as genotypic traits such as the presence of bap and blaPER-1 genes in twenty wound and eight environmental MDR A. baumannii isolates. While all strains were identified as good biofilm producers, no statistically significant correlation was detected between the examined traits and biofilm formation. However, differences in biofilm production were observed between environmental and wound isolates. The natural bile salts Na-cholate, Na-deoxycholate, and Na-chenodeoxycholate demonstrated effective anti-A. baumannii activity (MIC = 0.25-10 mg mL−1), with significant anti-biofilm effects. Na-deoxycholate and Na-chenodeoxycholate inhibited 94-100% of biofilm formation at super-MIC concentrations (8-32 mg mL−1). This study underscores the urgent need for innovative strategies to combat antibiotic resistance and biofilm formation in A. baumannii, highlighting the potential of natural bile salts as promising biofilm inhibitors and encouraging further research into their modification and combination with other antimicrobials.